Molecular diagnosis of Campylobacter in poultry chain intended for human consumption in Costa Rica. - Zumbado-Gutiérrez, Leana; Arévalo-Madrigal, Alejandra; Donado-Godoy, María del Pilar; Romero-Zúñiga, Juan José (Agronomía Mesoamericana, 2014)
The aim of this study was to determine the presence and frequency of Campylobacter jejuni and Campylobacter coli in three levels of the poultry chain production in Costa Rica. The levels studied were farms, slaughterhouse/processing plant, and retails of the Great Metropolitan Area of Costa Rica. For detection and isolation of Campylobacter sp., 84 samples from the poultry chain (24 chicken meat samples at retail, 20 carcass rinses and 40 caecum contents taken at slaughterhouse), obtained in November 2012, following the ISO 10272-1:2006 protocol, USDA modified (United States Department of Agriculture). From the 84 samples analyzed, 36 (42.8%) were positive for C. jejuni, and one (1.2%) for C. coli. The quantity of positive samples per sample type, according to Polimerase Chain Reaction (PCR), was: for caecal content, 16 (n=40), for carcass, 8 (n=20) and retail, 12 (n=24). Sixteen of the twenty farms sampled were positive. A high frequency of Campylobacter spp. at all sample points of the production chain was determined, which could be associated with modification of parameters related to food safety in each link. Rapid cooling measures and the use of chlorine in the cooling water at the process plant collaborate to decrease the frequency of Campylobacter positive samples.